2007
DOI: 10.1111/j.1440-1843.2007.01102.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostication in severe acute respiratory syndrome: A retrospective time‐course analysis of 1312 laboratory‐confirmed patients in Hong Kong

Abstract: This large-scale analysis identified important discriminatory parameters related to the patients' demographic profile (age and gender), severity of illness (pulse rate and neutrophil count), and multisystem derangement (platelet count, CPK, ALT and LDH), all of which prognosticated adverse outcomes during the SARS episode. While age, pulse rate and neutrophil count consistently remained significant prognosticators during the first 10 days of illness, the prognostic impact of other derangements was more time-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 26 publications
6
34
0
Order By: Relevance
“…Recent clinical research suggests that some patients have mild symptoms and can recover quickly, while others may develop rapid disease progression, which often leads to respiratory failure and even death. Besides, advanced age at presentation has shown to be very useful in predicting the mortality in SARS [9] and MERS [10] cases. Elderly patients tend to develop a greater number of comorbidities, potentially leading to poor outcomes [11].…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical research suggests that some patients have mild symptoms and can recover quickly, while others may develop rapid disease progression, which often leads to respiratory failure and even death. Besides, advanced age at presentation has shown to be very useful in predicting the mortality in SARS [9] and MERS [10] cases. Elderly patients tend to develop a greater number of comorbidities, potentially leading to poor outcomes [11].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoalbuminemia is a powerful predictor of mortality in patients with various illnesses, (1)(2)(3)(4)(5)(6) suggesting that either reduced availability of albumin or the underlying cause of hypoalbuminemia reduces survival. Albumin has a number of essential physiologic effects necessary for normal health such as vasodilatation, inhibition of endothelial cell apoptosis, antioxidant effects and reduced platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoalbuminemia is a reliable predictor of mortality in patients with various illnesses (1)(2)(3)(4)(5)(6) as well as a predictor of disability and mortality in healthy older adults. (7)(8)(9) The prognostic value of low serum albumin may reflect ongoing inflammation, malnutrition or loss of albumin's protective effects (vasodilatation, inhibition of endothelial cell apoptosis, antioxidant effects and reduced platelet aggregation).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with conditions such as malnutrition, chronic inflammation, enteropathy, or liver disease can have reduced serum albumin concentrations [4]. As a result, the serum albumin concentration can be considered an indicator of overall health, and studies have shown that a low serum albumin concentration is a strong predictor of mortality for various acute and chronic illnesses [5][6][7][8].…”
mentioning
confidence: 99%